Evaluasi Kesesuaian Lahan untuk Tanaman Kopi Robusta (Coffea canephora) di Desa Pajahan Kecamatan Pupuan Kabupaten Tabanan - DERMAWAN, SUTAN TANTOWI; MEGA, I MADE; KUSMIYARTI, TATI BUDI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Evaluation of Land Suitability for Robusta Coffee Plant (Coffea canephora) in Pajahan Village, Pupuan Sub-district, Tabanan Regency Robusta coffee (Coffea canephora) is one of the agricultural commodities that have a profitable prospect. Pupuan sub-district is concentrated of Robusta coffee in Bali Province. Pajahan Village is one of the 14 villages located in Pupuan sub-district which also built Robusta coffee. Based on data from the Central Bureau of Statistics (CBS) of Pupuan Sub-district, coffee production in Pajahan Village has continued to decline since 2012 until 2016. Evaluation of Land Suitability is a way to know the limiting factor in the research area. Land evaluation conducted by matching method between land characteristic / quality with growth requirement of plant evaluated. The research was conducted in Pajahan Village, Pupuan Subdistrict and Laboratory of Soil, Faculty of Agriculture - Udayana University. The research was conducted from October to December 2017. The results showed that the actual land suitability classes on the IILckK land unit is S3na2, IIILckK is S3na2.eh1 and IVLckK is Neh1. Fertilization, addition of organic matter, terracing and proper land cover can increase the class of land suitability to be appropriate marginal (S3) to very appropriate (S1). The limiting factor of dry season and moisture is a major limiting factor that can not be repaired.